ChIP-seq in studying epigenetic mechanisms of disease and promoting precision medicine: progresses and future directions. (September 2016) - Yan, Huihuang; Tian, Shulan; Slager, Susan L; Sun, Zhifu
Chromatin immunoprecipitation followed by sequencing (ChIP-seq) is widely used for mapping histone modifications, histone proteins, chromatin regulators, transcription factors and other DNA-binding proteins. It has played a significant role in our understanding of disease mechanisms and in exploring epigenetic changes for potential clinical applications. However, the conventional protocol requires large amounts of starting material and does not quantify the actual occupancy, limiting its applications in clinical settings. Herein we summarize the latest progresses in utilizing ChIP-seq to link epigenetic alterations to disease initiation and progression, and the implications in precision medicine. We provide an update on the newly developed ChIP-seq protocols, especially those suitable for scare clinical samples. Technical and analytical challenges are outlined together with recommendations for improvement. Finally, future directions in expediting ChIP-seq use in clinic are discussed.